Alginate hydrogels for bone tissue engineering, from injectables to bioprinting: A review - Hernández-González, Aurora C.; Téllez-Jurado, Lucía; Rodríguez-Lorenzo, Luis M. (Carbohydrate polymers, 2020)
[Display omitted] •Ionic gelling ability is a key parameter for alginate’s injectable biomaterials.•Alginate properties can be tuned by chemical modification and/or covalent bonding.•The biofabrication field for bone engineering is mainly based on alginate.•Organic-inorganic hybrid alginate materials are a promising alternative to study. This review focuses on recently developed alginate injectable hydrogels and alginate composites for applications in bone tissue regeneration, and it evaluates the alternatives to overcome the problems that avoid their utilization in the field. Section 2 covers the properties of alginates that have made them useful for medical applications, in particular their ionic gelling ability for preparing injectable compositions used as delivery drugs systems. The advantages and shortcomings of these preparations are revised together with the chemical modifications assayed. Section 3 describes how it has been taken advantage of alginates into the new field of biofabrication and the developments in bone engineering. The state of the art of this field is reviewed. Finally in Section 4, new developments and approaches that in opinion of the authors can lead to a breakthrough in bone tissue engineering using alginates are introduced.